V2CTX catalyzes polysulfide conversion to enhance the redox kinetics of Li–S batteries. Issue 6 (25th January 2022) - Han, Fengfeng; Jin, Qi; Xiao, Junpeng; Wu, Lili; Zhang, Xitian
Abstract : V2 CT X with a nanobelt structure was successfully prepared. A separator modified by V2 CT X and KB was designed to accelerate redox kinetics and realize long-term cycling stability. Abstract : Lithium–sulfur (Li–S) batteries have the potential to become the future energy storage system, yet they are plagued by sluggish redox kinetics. Therefore, enhancing the redox kinetics of polysulfides is key for the development of high-energy density and long-life Li–S batteries. Herein, a Ketjen Black (KB)/V2 CT X modified separator (KB/V2 CT X -PP) based on the catalytic effect in continuous solid-to-liquid-to-solid reactions is proposed to accelerate the conversion of sulfur species during the charge/discharge process in which the V2 CT X can enhance the redox kinetics and inhibit polysulfide shuttling. The cells assembled with KB/V2 CT X -PP achieve a gratifying first discharge capacity of 1236.1 mA h g −1 at 0.2C and the average capacity decay per cycle reaches 0.049% within 1000 cycles at 1C. The work provides an efficient idea to accelerate redox conversion and suppress shuttle effects by designing a multifunctional catalytic separator.